Detection of Lyme disease and anaplasmosis pathogens via PCR in Pennsylvania deer ked. Issue 2 (17th November 2016) - Buss, M.; Case, L.; Kearney, B.; Coleman, C.; Henning, J.D.
ABSTRACT: Borrelia burgdorferi and Anaplasma phagocytophilum are obligate intracellular parasites that maintain their life cycles in enzoonotic vector‐host cycles with Ixodes scapularis as a vector. In addition to ticks, the hosts are commonly infested with insects from the Hippoboscidae family. This study confirms the presence of B. burgdorferi and A. phagocytophilum in deer keds ( Lipoptena cervi) removed from white‐tailed deer using PCR. Detection of these pathogens in deer ked represents a potential novel susceptibility of wildlife and also suggests the risk of transmission of these pathogens to humans and animals alike through the bite of an infected ectoparasite. This study represents the first instance in the U.S. of detection of tick‐borne pathogens in a member of the Hippoboscid family.